Tumor priming using metronomic chemotherapy with neovasculature-targeted, nanoparticulate paclitaxel. (July 2016) - Luan, Xin; Guan, Ying-Yun; Lovell, Jonathan F.; Zhao, Mei; Lu, Qin; Liu, Ya-Rong; Liu, Hai-Jun; Gao, Yun-Ge; Dong, Xiao; Yang, Si-Cong; Zheng, Lin; Sun, Peng; et al.
Abstract: Normalization of the tumor microenvironment is a promising approach to render conventional chemotherapy more effective. Although passively targeted drug nanocarriers have been investigated to this end, actively targeted tumor priming remains to be explored. In this work, we demonstrate an effective tumor priming strategy using metronomic application of nanoparticles actively targeted to tumor neovasculature. F56 peptide-conjugated paclitaxel-loaded nanoparticles (F56-PTX-NP) were formulated from PEGylated polylactide using an oil in water emulsion approach. Metronomic F56-PTX-NP specifically targeted tumor vascular endothelial cells (ECs), pruned vessels with strong antiangiogenic activity and induced thrombospondin-1 (TSP-1) secretion from ECs. The treatment induced tumor vasculature normalization as evidenced by significantly increased coverage of basement membrane and pericytes. The tumor microenvironment was altered with enhanced pO2, lower interstitial fluid pressure, and enhanced vascular perfusion and doxorubicin delivery. A "normalization window" of at least 9 days was induced, which was longer than other approaches using antiangiogenic agents. Together, these results show that metronomic, actively-targeted nanomedicine can induce tumor vascular normalization and modulate the tumor microenvironment, opening a window of opportunity for effective combination chemotherapies.